WOMEN LEADERSHIP IN OPTICS FEMINIST INTERPRETATION - Bustanun Niam; Nasihkol Haromain; Muhammad As'ad (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2021)
This paper tries to make a discussion about women leadership perspective feminist interpretation. As is known, women leadership status until now is still invite a polemic morever for muasir-academis circles. On one side, there is a opinion that classic interpretation model about gender is considered irrilevent more with modern context. Because term of obscurity gender more take sides to men. And than in other side, movers feminist exaggerating in interpret many verses al-Qur’an for supporting their opinion. In al-Qur’an, the verse that always made reference when discussing about gender is QS. al-Nisa’ [4]: 34. This verse is considered as amplifier  by many  people that leadership must be in hand men. But is that true that the important message in this verse as like it ? are role women restricted in political realm ? Must be recognized that al-Qur’an (QS. al-Naml [27]: 20-44) has told about Queen Bilqis, she is woman phenomenal leader who succes changing Saba’ country become a prosperous country. In QS. al-Nisa’[4]: 34 and al-Naml [27]: 20-44 look contradicting, but actually not like that because each of these two verses tell different context. Irrespectively of many argument for movers feminism, discuss more about women leadership in their opinion is so interesting. At least, this paper attend for stopping long debate between twu stronghold, between patriarchism and feminism that have not find clarity.